Unusual Mechanisms of Penile Amputation. (28th December 2019) - Fazi, Julian; Adkins, David; Knight, Jennifer; Luchey, Adam
Abstract : Penile amputation is an uncommon and highly morbid injury. Many mechanisms have been reported ranging from self-mutilation and domestic violence to traumatic circumcisions. We present two unusual cases of traumatic penile amputation. An older gentleman endured extensive perineal trauma after being trapped underneath an industrial-sized lawnmower, and a young adolescent was bitten by an English bulldog and suffered amputation of the glans of his penis. These unique and very different cases of penile amputation highlight differences in operative managements, complications, and reconstructive possibilities.